1999
DOI: 10.1007/bf02494844
|View full text |Cite
|
Sign up to set email alerts
|

Photoaddition of water and methanol to 2,2,4,6-tetramethyl-1,2-dihydroquinoline

Abstract: Products of the steady-state photolysis of 2,2,4,6-tetramethyl-1,2-dihydroquinoline (1) in water, methanol, and water--ethanol were isolated for the first time and identified by IH and J3C NMR spectroscopy, IR spectroscopy, and mass spectrometry. As a result of the photolysis, the molecule of the solvent is added to the double bond of the heterocycle with formation of 4-hydroxy-(2) or 4-methoxy-2,2,4,6-tetramethyl-1,2,3,4-tetrahydroquinoline (3) in water and methanol, respectively. Compounds 2 and 3 are conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The steady-state photolysis of 1 in the SDS micellar solutions is similar to photolysis in aqueous solutions: the quantitative formation of product characterized by a UV spectrum similar to the spectrum of the hydroxy adduct formed in water ( λ max = 305, 245, and 214 nm) [6] is observed. Qualitatively, the kinetic regularities of the reaction and the intermediate species generated in the flash photolysis are similar to those observed in water: intermediate species decay is a pseudofirst-order reaction, and the intermediate species structure depends drastically on pH.…”
Section: Dhq Photolysis In Micellar Solutions Of the Anionic Surfactantmentioning
confidence: 75%
See 1 more Smart Citation
“…The steady-state photolysis of 1 in the SDS micellar solutions is similar to photolysis in aqueous solutions: the quantitative formation of product characterized by a UV spectrum similar to the spectrum of the hydroxy adduct formed in water ( λ max = 305, 245, and 214 nm) [6] is observed. Qualitatively, the kinetic regularities of the reaction and the intermediate species generated in the flash photolysis are similar to those observed in water: intermediate species decay is a pseudofirst-order reaction, and the intermediate species structure depends drastically on pH.…”
Section: Dhq Photolysis In Micellar Solutions Of the Anionic Surfactantmentioning
confidence: 75%
“…Detailed studies of the photolysis mechanism for 2,2,4-trimethyl-1,2-dihydroquinolines (DHQ) with alkyl and alkoxy substituents in the C(6) and C (8) positions of the aromatic ring showed that the reaction mechanism in water and methanol is radically different [6][7][8]. In these solvents, no aminyl radicals are generated under irradiation and the primary photochemical reaction is double proton transfer from the water or methanol molecule to the excited singlet DHQ molecule ( S 1 ) in the C(3) position of the heterocycle and from the N-H bond to the solvent (Scheme 1).…”
mentioning
confidence: 99%
“…1), which is characteristic of the CC generated from 1,2 dihydro quinolines. [15][16][17][18][19] When comparing the absorption intensi ties of the CC at 480 nm in methanol and the triplet state of benzophenone at 525 nm in benzene (quantum yield 100%, molar absorption coefficient 7200 L mol -1 cm -1 ) 27 detected upon the laser photolysis of the corresponding solutions with the same absorbance at the excitation wave length, we obtain the molar absorption coefficient of the CC equal to ∼4000 L mol -1 cm -1 if the quantum yield of the CC is 40%. 18, 19 The kinetics of CC decay is described by a law corre sponding to parallel reactions of the first and second or ders.…”
Section: Resultsmentioning
confidence: 97%
“…The preparative-scale steady-state photolysis was carried out, products 2 and 3 were isolated and analyzed by 1 H and 13 C NMR, IR, and mass-spectroscopy [8]. The analysis of the structure of compounds 2 and 3 has shown that corresponding tetrahydroquinoline is formed as a result of the addition of solvent to the double bond of heterocycle.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of the conversion depends on the solvent, concentration, and weakly on the temperature [8].…”
Section: Resultsmentioning
confidence: 99%